(untitled) (Proceedings of International Educators Conference, 2024)
2-nitroso-1-naphthol was selected as an organik analytical reagent for the content of cobalt ions in the wastewater of industrial and environmental facilities of Almalyksky KMK JSC. It has been shown that 2-Nitroso-1-naphthol immobilizes an organik reagent on various fibrous carriers, detecting cobalt ions, as well as an express detection method.